The prolyl isomerase FKBP25 regulates microtubule polymerization impacting cell cycle progression and genomic stability. Issue 5 (18th January 2018) - Dilworth, David; Gudavicius, Geoff; Xu, Xiaoxue; Boyce, Andrew K J; O'Sullivan, Connor; Serpa, Jason J; Bilenky, Misha; Petrochenko, Evgeniy V; Borchers, Christoph H; Hirst, Martin; Swayne, Leigh Anne; Howard, Perry; et al.
Abstract: FK506 binding proteins (FKBPs) catalyze the interconversion of cis-trans proline conformers in proteins. Importantly, FK506 drugs have anti-cancer and neuroprotective properties, but the effectors and mechanisms underpinning these properties are not well understood because the cellular function(s) of most FKBP proteins are unclear. FKBP25 is a nuclear prolyl isomerase that interacts directly with nucleic acids and is associated with several DNA/RNA binding proteins. Here, we show the catalytic FKBP domain binds microtubules (MTs) directly to promote their polymerization and stabilize the MT network. Furthermore, FKBP25 associates with the mitotic spindle and regulates entry into mitosis. This interaction is important for mitotic spindle dynamics, as we observe increased chromosome instability in FKBP25 knockdown cells. Finally, we provide evidence that FKBP25 association with chromatin is cell-cycle regulated by Protein Kinase C phosphorylation. This disrupts FKBP25–DNA contacts during mitosis while maintaining its interaction with the spindle apparatus. Collectively, these data support a model where FKBP25 association with chromatin and MTs is carefully choreographed to ensure faithful genome duplication. Additionally, they highlight that FKBP25 is a MT-associated FK506 receptor and potential therapeutic target in MT-associated diseases.